Residential Care Development in California: History and Policy. (February 2022) - Frochen, Stephen; Ailshire, Jennifer; Pynoos, Jon
This literature review provides a framework for understanding the development of residential care in California, including state licensing, federal funding, and state and local planning policies for the development of facilities. It discusses the history, planning, and licensing of residential care as a home and community-based service in California. It examines the historic and innovative federal programs supporting assisted living in public or affordable housing, the public equivalent of residential care. Finally, it describes how the California housing crisis has prompted a new and sweeping set of state and local planning policies encouraging its development.